Penguatan Sikap Bela Negara Melalui Kegiatan Study Tour Museum Pahlawan - Eka Nor Shoviana; Siti Mundiro; Indah Luthfiana; Muhammad Nofan Zulfahmi (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the role of study tour activities to the Heroes Museum in strengthening students' national defense attitudes. In the digital era, many young generations lack awareness of national values ​​and the history of the nation's struggle. This is indicated by the low appreciation of the services of the heroes. The Heroes Museum as a historical education space has strategic potential in instilling patriotic values ​​through direct experience. Using the literature study method, this study collected data from books and scientific articles. The results show that experience-based activities, such as museum visits, are effective in increasing students' understanding of history, heroic values, and nationalism. In addition, museum visits can build students' character, such as a sense of responsibility, discipline, and love for the country. This study concludes that a study tour to the Heroes Museum not only enriches students' historical insights, but also instills moral values ​​and builds national identity in depth.